Faktor Kerentanan Banjir Rob Kecamatan Medan Belawan Kota Medan - Putri Zandiba Siregar; Ahmad Perwira Mulia; Gina Cynthia Raphita Hasibuan (Jurnal Syntax Admiration, 2023)
The rise in sea level has impacted the emergence of a flood disaster in the district of Belawan City Field. The flooding of these robs caused the sinking of settlements, industries and ports. The height of flooding that increases every year has an impact on the increased shortages caused and increased economic losses of communities working in vulnerable sectors. Therefore, vulnerability factors are necessary to determine effective adaptation directions. The research was carried out in the district of the Field of Belawan City of Medan where there are 6 (six) floods affected by the flood of rob: the Kelurahan Belawa I, Belawana II, Blawan Bahari, Balawan Pulau Sicanang and Bagan Deli. The study begins with the theoretical and empirical formulation related to vulnerability to flood areas followed by interviews with stakeholders aimed at finding issues more openly in which the interviewed parties are asked for opinions. The stakeholder used is the stakeholder who knows the phenomenon of the flooding of rob that occurs in the research area consists of 3 (three) groups representing the government and society. Factors affecting the level of vulnerability to flooding in the area are grouped into physical, social, economic and environmental vulnerability factors.